Firefight - Wheeler, Alex. (New York : Scholastic, 2009)
Deadly assassin X-7 hires six pilots from across the galaxy to help him complete his mission against the Red Squadron, but one of the pilots harbors a secret that could thwart X-7's plan.
"Lucas books."
5.8
3-6
3-6
Keywords: Skywalker, Luke (Fictitious character) -- Juvenile fiction; Life on other planets -- Juvenile fiction; Space warfare -- Juvenile fiction; Good and evil -- Juvenile fiction; Skywalker, Luke (Fictitious character) -- Fiction; Life on other planets -- Fiction; Space warfare -- Fiction; Good and evil -- Fiction; Science fiction; Skywalker, Luke (Fictional character) -- Fiction; Life on other planets -- Fiction; Space warfare -- Fiction; Good and evil -- Fiction; Science fiction; Star Wars fiction; Science fiction